2014
DOI: 10.1080/0965254x.2014.914074
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hospital customer orientation on burnout of public hospital service workers in New Zealand

Abstract: Using data from frontline hospital employees (FHEs) in a major New Zealand public hospital, this study expands previous research on the relationship between job demand stressors and burnout, and examines the role of customer orientation (CO) as an organisational level variable in the burnout process. The study results show that burnout symptoms partially mediate the effects of job demand stressors on FHEs self-evaluation of their ability to do their job. Besides having a direct negative impact on depersonalisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 128 publications
0
4
0
1
Order By: Relevance
“…Drawing upon previous studies on firms' MO, we explored whether firm age, firm size, or type of industry had any influence over the hypothesised theoretical linkages (Alteren & Tudoran, 2015;Bao, Fong, Landry, & Zhou, 2015;Laukkanen, Tuominen, Reijonen, & Hirvonen, 2016;Rod & Ashill, 2015;Ziggers & Henseler, 2016). To determine the age of the firm, firms were separated into two groups with 10 years of operations as the demarcation line (mean age was 9.35 years).…”
Section: Effects Of Firm Age and Sizementioning
confidence: 99%
“…Drawing upon previous studies on firms' MO, we explored whether firm age, firm size, or type of industry had any influence over the hypothesised theoretical linkages (Alteren & Tudoran, 2015;Bao, Fong, Landry, & Zhou, 2015;Laukkanen, Tuominen, Reijonen, & Hirvonen, 2016;Rod & Ashill, 2015;Ziggers & Henseler, 2016). To determine the age of the firm, firms were separated into two groups with 10 years of operations as the demarcation line (mean age was 9.35 years).…”
Section: Effects Of Firm Age and Sizementioning
confidence: 99%
“…Drawing upon previous studies on firm's CO, it was examined whether firm size, age of the firm and industry demonstrated any influence over the hypothesised theoretical linkages (Alteren & Tudoran, 2015;Bao et al, 2015;Rod & Ashill, 2015;Ziggers & Henseler, 2015). The firm size has been determined through number of employees, where firm with less than 100 employees is stratified as small (n=151), 101 to 500 employees as medium (n=75) and more than 500 employees is large (n=209) (Hooley, Greenley, Cadogan, & Fahy, 2005).…”
Section: Post Hoc Analysismentioning
confidence: 99%
“…According to a recent survey, this approach is warranted, as 69% of 'employees say COVID19 is the most stressful time of their career' (Human Resource Executive, 2020). Stressed-out workers are usually less productive and more distracted during challenging times, which customers may sense, thereby contributing to their own stress (Rod & Ashill, 2015;Roy & Eshghi, 2013). Moreover, supply chains are facing their biggest shock since World War II (Transport Times, 2020), which has caused immediate shortages and may have longer-term effects.…”
Section: Collective Excitement: Consequence-based/consumers Goodsmentioning
confidence: 99%